2004
DOI: 10.1021/ie0342560
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Ultrasonic Spectroscopy Study of the Nucleation and Growth of Copper Sulfate Pentahydrate Batch Crystallized from Supersaturated Aqueous Solutions

Abstract: In situ ultrasonic attenuation spectroscopy is applied to the challenging case of monitoring the nucleation and growth of copper sulfate pentahydrate crystallized from supersaturated aqueous solutions, a system not readily amenable to analysis via optical methods due to the intense blue color of the saturated crystallizing solution. In experiments in the 2.8-L rectilinear reactor of a spectrometer, crystallization and dissolution points are reliably detected from the measured attenuation spectra. There are min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Comparison with SEM especially revealed that US spectroscopy reflects reality the best. The importance of the crystallization mechanism can be emphasized with regard to a study by Wilkinson et al . who investigated the crystallization of copper sulfate pentahydrate in a similar way as Tebbutt et al , Their results showed that the crystal size was strongly influenced by the cooling rate; however, at a size of roughly 300 μm the crystals break resulting in a similar PSD independent of the cooling rate.…”
Section: Methodsmentioning
confidence: 99%
“…Comparison with SEM especially revealed that US spectroscopy reflects reality the best. The importance of the crystallization mechanism can be emphasized with regard to a study by Wilkinson et al . who investigated the crystallization of copper sulfate pentahydrate in a similar way as Tebbutt et al , Their results showed that the crystal size was strongly influenced by the cooling rate; however, at a size of roughly 300 μm the crystals break resulting in a similar PSD independent of the cooling rate.…”
Section: Methodsmentioning
confidence: 99%
“…For example, we have sized whole milk, separately sizing the protein particle size distribution and that of the milk fat globules [31] [32]. Attempts to use this technique to size crystals during growth have not been overly successful despite considerable effort [33][34][35][36][37][38][39][40][41]because the phase transition itself introduces an additional attenuation term, over and above the scattering terms [30] [42](thermal and visco-inertial) currently included in the inversion models. As a result, empirical methods of analysis were resorted to which suffered from the complicated and variable interaction between the ultrasound field and the crystallising material, we now know that the quasi-continuous acoustic fields can modify the crystal nucleation process [43] and Section 4.3.1 below, An advantage that ultrasound attenuation spectroscopy enjoys over light scattering techniques is its ability to measure concentrated systems and in stirred conditions, so that the emergence of structure can be followed over time.…”
Section: Ultrasound Attenuation Spectroscopymentioning
confidence: 99%
“…Several studies have investigated the solid–liquid equilibrium and crystallization of the copper sulfate pentahydrate (CuSO 4 ·5H 2 O). Giulietti et al presented a study of batch cooling experiments, from 70 to 30 °C, some of which included 2% free acid. They concluded that programmed cooling produced larger crystals than linear cooling.…”
Section: Introductionmentioning
confidence: 99%